ARCHITECTURE AND URBAN PLANNING DURING SOVIET UNION - Axmedov To'lqin (Journals Park Publishing, 2022)
The article covers the facts of the loss of its attractiveness during the Union of architecture, which has developed on a legislative basis, which has been inherent in it for thousands of years, the actions of the Bolsheviks to their advantage in the way of their goals-as a result of which architecture loses its identity and the beauty and charm of large.
Keywords: villages and farms, revolutions, exploiters, monuments, soviet architecture, architectural ensembles, quarters, thematic composition